Preparation and characterization of an alkali‐pickled preserved egg white heat‐induced gel. (19th July 2022) - Ye, Yang; Li, Anjiao; Feng, Tingting; Yuan, Xianling; Xiao, Xia; Wang, Yang
Abstract: In recent years, heavy‐metal salts for pickling preserved eggs and the long production period have affected its acceptability and industrialization. In this study, we used the method of short‐term pickling of no‐heavy‐metal salts to obtain gels by alkali‐picked and heat induced. The physicochemical properties, secondary structure and free amino acid composition of egg whites during pickling were determined. Furthermore, the texture and chromatic characters of the preserved egg white gels after heating were analyzed. After 7 days of pickling, the pH and free alkalinity can reach the level of preserved eggs, presenting the value of 11.48 and 184.03 mg/100 g respectively. The α‐helix content decreased from 36.01% to 32.39%. On the other hand, the β‐turns increased from 16.98% to 18.82%, and the Random coils increased from 26.31% to 28.76%. The free sulfhydryl content of preserved egg white increased gradually, whereas the total sulfhydryl content, the T d value, and free amino acid content decreased during the pickling process. The hardness and springiness of the gel remained largely unchanged during the pickling time (5–8 days). The gel's appearance, chromatic, and texture reached the level of traditional preserved egg in a relatively short pickling time, providing a new idea for the rapid picking of preserved egg white gel. The treatment in this study is important for improving the efficiency of industrial production of preserved egg white gels. Practical applications: Heat treatment is a standard method in food processing, helping improve the texture and quality of products. After heat treatment, the physicochemical properties of the alkali‐pickled eggs can reach the state of traditionally preserved egg whites. Therefore, the method described in this study can help shorten the pickling time of preserved egg white products and provide theoretical support for developing new preserved egg products.